Resilience among Universiti Sains Malaysia nursing students - Ali, Noorsyafawani Mohamed (Universiti Sains Malaysia, 2023)
Resilience is a term commonly used to describe the ability to turn adversity into opportunities and learn from demanding situations. Resilience has emerged as a concept that can explain and predict students' academic success and well-being in stressful and traumatic situations. Thus, this study was aimed to determine the level of resilience among USM nursing students. The cross-sectional study was used were 174 nursing students from USM Health campus involved in completing a self-administered questionnaire adopting from Trait and State Resilience scale. The finding from this study shows that 56 (32.2%) of the nursing students have a very high level of trait resilience, and only 3 (1.7%) have low trait resilience. For state resilience, 81 (46.6%%) of the nursing students have a very high level of state resilience and only 1 (0.6%) have low state resilience. The mean trait resilience score was 66.07 (SD: 11.7) and the mean state resilience score was 59.24 (SD: 9.3). There was a significant, moderate and positive correlation between trait resilience scores and state resilience scores which is tested using Pearson correlation test (Pearson’s r= 0.733, p value <0.001). In conclusion, the study of the level of resilience shows a high level of trait resilience and very high state resilience among USM nursing students. However, further research should be conducted in a large sample size to compare the level of resilience among nursing students in university and investigate other probable factors that affect the resilience of nursing students including internal factor.